(untitled) (Journal of Human Sciences, 2024)
During the Spanish Civil War (1936-1939), the Francoist authorities organized three pilgrimage trips for Moroccans from the Northern Zone (Spanish protectorate in Morocco). Coordination was established with the Italian authorities to transport Libyan pilgrims on the same ship carrying the Moroccans. These journeys resulted in the creation of two travel texts documenting the pilgrimages, providing important historical information about the North African countries the trips passed through on their way to the holy lands (Libya, Egypt). Additionally, they offer details about the European countries sponsoring these trips (Spain, Italy).